DEVELOPMENT OF BIOLOGY LEARNING MODULE BASED ON SCIENTIFIC APPROACH ON RESPIRATORY SYSTEM TOPIC IN SENIOR HIGH SCHOOL - Alone Marera (Al-AHYA: Jurnal Pendidikan Biologi, 2019)
The kind of this research was research and development (R & D) which aimed to understand the development process, validity, practicality, and effectiveness of biology learning module based on scientific approach on respiratory system topic in senior high school. Research and development phase referred to ADDIE development model that consist of 5 phases: (1) Analysis, (2) Design, (3) Development,                          (4) Implementation, and (5) Evaluation. This research used 3 kinds of instruments: (1) expert validation sheet to assess the validity of the module, (2) teacher and student response sheet to assess the practicality of the module, and (3) posttest to assess the effectiveness of the module. Based on the result of data analysis, the average of module validity from 2 validators was 4,3 and the module categorizied as valid. The average percentage response score from 3 teachers was 89,3% (very positive) and the average percentage of response score from 25 students was 86,0% (very positive) and the module was categorizied as practical. From the posttest, obtained 21 students or 84% of students were able to achieve the criteria of learning mastery and the module was categorizied as effective. Therefore, can be concluded that development process of biology learning modul based on scientific approach on respiratory system topic in senior high school referred to ADDIE development model and qualified valid, practical, and effective.  Keywords: Biology Module, Scientific